Numerical investigation on the effect of blood flow induced vibration on bileflet artificial heart valve by using fluid structure interaction technique - Kadhim, S.K. (Asian Research Publishing Network, 2017)
Surgeries for replacement of artificial heart valves became more common and frequently used because of artificial heart valve failure. Determining the reason of the failure and finding suitable solutions require deep knowledge about artificial heart valve behavior and operation. The reasons of valve failure are related to the patient's body and the valve design. The compatibility of the valve to a human body is associated with the dynamics of blood flow and the materials used to manufacture the valve. When blood flows through the arteries and valves, blood exerts forces at the valve components, thereby causing flow-induced vibration, which may damage the valve. In this study, fluid-structure interaction techniques to computational fluid dynamics analysis were used to investigate the effects of vibrations occurring via computer simulation. To obtain the optimal design of shear stress, the shear stress of the connection pin of an artificial heart valve were calculated and compared with the shear stress of the connection pin in the literature. At Reynolds number of 250, the excitation frequencies increased from 94.24 rad/sec to 126.9 rad/sec, which resulted in a 75 increase in shear stress values at the connection pin valve at a fully closed angle of 85°. The increase in frequency may cause resonance phenomenon, which will cause damage to the artificial heart valve components. Consequently, the blood components will also be damaged, thereby causing an increase in blood clogging occurrence downstream of the artificial heart valve. © 2006-2017 Asian Research Publishing Network (ARPN).